STUDI KOMPARASI HASIL BELAJAR MATEMATIKA MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) DAN STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) - Sri Fatoyah; Akhmad Nayazik; Arie Wahyuni (Jurnal Ilmiah Pendidikan Matematika Al Qalasadi, 2020)
Abstract This study aims to find out which is better between mathematics learning outcomes in Cokroaminoto Batang Junior High School students who are taught using the Cooperative learning model Numbered Head Together (NHT) or those who are taught using the Cooperative learning model type Student Teams Achievement Division (STAD) in the material mathematics field rectangular. The sample of this study consisted of 2 classes, namely experimental class 1 and experimental class 2 using the NHT and STAD methods. This study used qualitative research methods. Data collection methods used are documentation and test methods. Research instruments in the form of learning tools and mathematics test results. Data analysis performed was a prerequisite test using the average similarity test and hypothesis testing by calculating the average. The results showed that the average learning outcomes of experimental class 1 students amounted to 76,875 and experimental class 2 amounted to 72,56667 which means that classroom learning outcomes taught by NHT type cooperative learning models were better than classroom learning outcomes taught by the STAD type cooperative learning models. From the results of the study, it can be concluded that the NHT type of cooperative learning model is more effective when compared to the STAD type cooperative learning model on the subject of quadrilateral in class VII students of Cokroaminoto Batang Middle School Academic Year 2018/2019 Keywords: STAD type cooperative learning model, NHT type cooperative learning model, learning outcomes .